RANCANG BANGUN SISTEM TRACKING JASA LAUNDRY SEPATU DI CLINIX SHOES CARE BERBASIS WEBSITE - Febriyan Saragih; Yulia Agustina Dalimunthe; Husni Lubis (Universitas Methodist Indonesia, 2021)
The matter of time still being an important thing in a shoe’s laundry services, because it can take a long time to get a shoes laundry. That’s why it required a tracking system to checking a status from our shoes at the clinix shoes and care laundry. The making of this system uses the method, waterfall starting from requirements analysis, system design, writing program code, testing programs, implementing programs, and writing program code in a structured manner. Writing program code using PHP, MySQL database and using the framework. With Codeigniter 3 this tracking system, customers can input the receipts provided by the admin clinix shoes care, to find out the status of shoes being laundered, and in this tracking system the customer can also check rates laundry.